Estimation of dental age in panoramic radiographs in children and adoloescents from 7-17 years through Demirjian method, Cuenca – Ecuador. (International Journal of Medical and Surgical Sciences, 2017)
Age is an indicator of dental somatic maturation, of clinical importance in dentistry for planning the treatment of growing patients. The Demirjian method is the most widely disseminated to estimate dental age. With this method, numerous studies have been carried out in different ethnic groups, analyzing European, Asian and American children, among others. These results suggest possible differences in dental maturation patterns between different populations. The aim of the present study was to correlate the dental age, using the Demirjian method, with the chronological age according to gender in a group of children who attended the Radiological Center “Innova” located in Cuenca-Ecuador in the period 2012 - 2014, This study was descriptive, retrospective and analytical, in which a sample stratified by age and gender was selected, including 362 radiographs, of which 205 are female and 157 male. An inter-class correlation coefficient was obtained, as a measure of correlation between dental and chronological age, of 0.830 in the female gender and 0.801 in the male gender. In general, Demirjian’s method tended to underestimate dental age in girls and boys in a similar way. In conclusion, the results obtained in the present work do not coincide with many places in the world, that is, the dental age in this group was slightly lower in both girls and boys than the original Franco - Canadian sample. The obtained range of dental age is not similar to the chronological age but the degree of correlation between both is adequate to apply in our population, presenting itself in the same way according to gender, so a standard table for the population was elaborated Cuencana. We consider that the Demirjian method is applicable to this sample of children using the database proposed in the present investigation.